Tissue Oxygen Tension Monitoring of Organ Perfusion: Rationale, Methodologies, and Literature Review. Issue 3 (June 2016) - de Santis, V.; Singer, M
Abstract : (Abstracted from Br J Anaesth, 115:357–365, 2015) Tissue oxygen tension (tPO2 ) monitoring is important because tPO2 represents the balance between local oxygen delivery and consumption at any given time and thus indicates adequate regional perfusion of tissues in the human body. In this current study, the authors examined the clinical use of bladder tPO2 monitoring and reviewed available methodologies.